2018
DOI: 10.1371/journal.ppat.1007316
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Sfl1/Sfl2 regulatory network drives the formation of pathogenic microcolonies

Abstract: Candida albicans is an opportunistic fungal pathogen that can infect oral mucosal surfaces while being under continuous flow from saliva. Under specific conditions, C. albicans will form microcolonies that more closely resemble the biofilms formed in vivo than standard in vitro biofilm models. However, very little is known about these microcolonies, particularly genomic differences between these specialized biofilm structures and the traditional in vitro biofilms. In this study, we used a novel flow system, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Briefly, 5 × 10 4 cells/well were incubated for 2 and 4 hr to allow formation of short hyphae. In parallel, to measure long hyphae in vitro, 100 cells/well were incubated for 24 hr to generate microcolonies originating from single yeast cells that formed radially branching filamentous hyphae (McCall, Kumar, & Edgerton, ). Following this, cells were fixed by adding one‐tenth of the volume of 37% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 5 × 10 4 cells/well were incubated for 2 and 4 hr to allow formation of short hyphae. In parallel, to measure long hyphae in vitro, 100 cells/well were incubated for 24 hr to generate microcolonies originating from single yeast cells that formed radially branching filamentous hyphae (McCall, Kumar, & Edgerton, ). Following this, cells were fixed by adding one‐tenth of the volume of 37% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of SFL1 gene almost fully abolished biofilm formation prompted by C. albicans cells under acidic conditions (pH 4) (Fig 4A), consistent with this regulator being a critical player in the reprogramming of genomic expression under those conditions. Recently, Sfl1 was found to be required for formation of microcolonies contributing to maximal adhesion to epithelial cells [37]. The involvement of Sfl1 in formation of acidic biofilms represents a further insight into the biological function of this regulator.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are required to fully characterize the role of Sfl1 in regulating gene expression during formation of acidic biofilms and, in particular, to identify Sfl1-regulated targets that are essential for biofilm formation. Although Sfl1 has been mostly described as a transcriptional repressor in C. albicans [37,39], evidences from chromatin immunoprecipitation profiling have shown that it also acts as a positive regulator [38]. Similarly, the ScSfl1 orthologue has also been found to have a dual effect acting both as a positive and a negative regulator [40].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these straight tubular hyphae, sinusoidal or helical hyphal growth has been reported in C. albicans when cultivated on surfaces (Sherwood-Higham et al, 1994;Brand et al, 2009;McCall et al, 2018), and are associated with antifungal resistance (Sherwood-Higham et al, 1994). However, hyphae are not solely a morphological switch, but they are also associated with important transcriptional regulation of virulence factors including secreted aspartyl protease, adhesins and superoxide dismutase (Mayer et al, 2013), and, more recently, the cytotoxic peptide candidalysin encoded by ECE1 (Moyes et al, 2016).…”
Section: Yeast-to-hyphal Transitionmentioning
confidence: 99%
“…However, since then, C. albicans has been described to exist in eight different morphotypes including four yeast morphologies (white, opaque, gray, and gut), two hyphal morphologies (linear and sinusoidal), pseudo-hyphae, and chlamydospores (Hayes, 1966;Slutsky et al, 1987;Brand et al, 2009;Pande et al, 2013;Tao et al, 2014). In addition to this large diversity in shape, C. albicans can also exist in unicellular culture, biofilms, and micro-colonies (McCall et al, 2018). This polymorphic nature of C. albicans is a great example of a protean organism.…”
Section: Introductionmentioning
confidence: 99%